BUSY PERIOD AND NUMBER OF CUSTOMERS SERVED DURING THE BUSY PERIOD IN A \(Geo^X/G_D/1\) QUEUEING SYSTEM - Georgieva, Magdalena; Bakeva, Verica (Matematichki Bilten, 2000)
The queueing systems \(Geo^X/G_D/1\), i.e. systems with geometrical distributed input stream, group arrivals and discrete service times, are considered in this paper. Using the method of collective marks, the distribution of the busy period and the number of customers serviced during the busy period are determinated.